Dual-task interference is related to attentional level in healthy farmers: An observational study. Issue 27 (2nd July 2020) - Shin, Dabi; Kang, Eun Kyoung
Abstract : Abstract: Dual-task interference (DTI) is a decreased performance when conducting 2 tasks simultaneously, such as cognitive and motor tasks. This study aimed to identify the DTI-related factors with individually computerized interference and analyze the relative implications of decreasing DTI in healthy farmers. It followed 3 computerized experiments: cognitive task (CT): release button 1 (BT1) as rapidly as possible when the word and color matched, motor task (MT): release BT1 and then tap button 2 (BT2) 10 times as rapidly as possible when "O" was presented, and dual tasks (DT): combination of CT and MT elements. The reaction time of correct releases (CRT) of BT1 in all tasks was measured, and the CRT ratios of DT were divided by the CRT values from CT and MT to obtain the DTI value. CRT during CT and MT was decreased compared to that during DT. The interference by CT (CRT of DT/CRT of MT × 100, CTI) was increased compared to the interference by MT (CRT of DT/CRT of CT×100, MTI). Additionally, comprehensive baseline characteristics, body composition, psycho-cognitive, and physical factors were assessed. Of a total of 54 participants, 16 are males (67.2 ± 8.9 years) and 38 females (62.5 ± 6.6 years). CTI showed significant correlations with age (r = 0.436, P  < .001), farming period (r = 0.290, P  = .033), score of the Mini-Mental State Examination in the Korean version of CERAD Assessment Packet (r = −0.329, P  = .015), CRT of the Go/No-Go test (r = 0.67, P  < .001), score of the short physical performance battery (r = −0.304, P  = .026), and time of the timed up and go test (r = 0.364, P  = .007). Regression analysis showed that the CRT of the Go/No-Go test (β = 0.558, P  < .001) was the most explanatory factors for CTI. Based on the individualized DTI values quantified, interference during cognitive task was mostly related to CRT of Go/No-Go test, reflecting the attentional level. These results could suggest strategies for the active attentional training to reduce DTI and passive simplification and modification of lifestyles.